Empowering Tri‐Functional Palladium's Catalytic Activity and Durability in Electrocatalytic Formic Acid Oxidation Reaction via Innovative Self‐Caging and Alloying Strategies - Chan‐Woo Lee; Sun Young Jung; Jeong Ho Ryu; Gyeom Seong Jeon; Ashish Gaur; Min Su Cho; Ghulam Ali; Mingony Kim; Kyung Yoon Chung; Arpan Kumar Nayak; Seoyoon Shin; Jiseok Kwon; et al. (Advanced Science)
Abstract Direct formic acid fuel cells (DFAFCs) stand out for portable electronic devices owing to their ease of handling, abundant fuel availability, and high theoretical open circuit potential. However, the practical application of DFAFCs is hindered by the unsatisfactory performance of electrocatalysts for the sluggish anodic formic acid oxidation reaction (FAOR). Palladium (Pd) based nanomaterials have shown promise for FAOR due to their highly selective reaction mechanism, but maintaining high electrocatalytic durability remains challenging. In this study, a novel Pd‐based electrocatalyst (UiO‐Pd‐E) is reported with exceptional durability and activity for FAOR, which can be attributed to the Pd nanoparticles encapsulated within a carbon framework where concurrent chemical alloying of Pd and Zr occurs. Further, the UiO‐Pd‐E demonstrates noteworthy multifunctionality in various electrochemical reactions including electrocatalytic ethanol oxidation reaction (EOR) and oxygen reduction reaction (ORR) in addition to the FAOR, highlighting its practical potentials.